Efek Pelatihan Relaksasi Untuk Menurunkan Stres Kerja Pada Karyawan Di. Pt Madubaru Yogyakarta - Sagala, Masitah (Fakultas Psikologi Universitas Ahmad Dahlan Yogyakarta, 2013)
ABSTRACTThe aim of this researches is to examine the effectiveness of relaxation training in order to reduce the job stress in employee of PT. Madubaru Yogyakarta. This researches using experimental researches with one group pretest postest design. WithÂ 11 subject. The result of study shows that score before experiment (pretest), Level of job stres employee in administrative personnel is 54, 5% in category medium, a total of 5 subjek is 45,5% in the category of high. After relaxation training (posttest), subject that have high job stress there was decrease 100% with 11 subject.Analysis of data using different test there is Wicolxon Signed Rank Test. The result different test wilcolxon signed rank test showing that score of Z = -2, 936 and p= 0,003 (< 0,05), this means that there are differences in job stress before and after the relaxation training. This result indicate that providing the relaxation training to employees significantly can reduce the job stress.Â Key Words : Job Stress, Training of Relaxation